دور آلية ضمان القروض في دعم وإنشاء المؤسسات الصغيرة والمتوسطة في الجزائر - حجاب, عيسى; بوسدرة, فوزي; بوخرص, عبد الحفيظ (Revue Internationale des Sciences de Gestion, 2020)
This article aims to highlight the role of loan guarantee funds as a mechanism in order to contribute to alleviating the problem of financing SMEs. Algeria has established several funds in line with the nature of this type of institutions, namely: the Loan Guarantee Fund for Small and Medium Enterprises (FGAR). Guaranteeing loans for investments of small and medium enterprises (CGCI-PME), the study found that these two funds have contributed significantly to support these institutions, where the first fund provided guarantees coverage amounted to 9.94 billion DA, while the second fund provided guarantees worth more than 66.4 billion DA.